Endoscopic treatment for persistent dysphagia after heller myotomy in a patient with spastic type of achalasia with the use of the intraoperative high-resolution manometry - A. A. Smirnov; N. V. Konkina; M. M. Kiriltseva; M. E. Lyubchenko; L. I. Davletbaeva; D. I. Vasilevskiy; A. Yu. Korolkov (Вестник хирургии имени И.И. Грекова)
A Peroral Endoscopic Myotomy was performed on the patient with the persistent dysphagia despite preceding Heller myotomy combined with partial fundoplication, relaparotomy, fundoplication wrap reconstruction, gastrostomy and left-sided thoracoscopy with the drainage of the thoracic abscess. The use of intraoperative High-Resolution Manometry during Endoscopic Peroral Myotomy helped to reveal the reasons for the failure of previous treatment and to address the dysphagia.